(untitled) (Conference Zone, 2022)
This article is devoted to the study of teaching methods and the creation of the discipline “Information technologies in education” in pedagogical higher educational institutions on the basis of electronic information and educational resources in the process of digitization. In the process of digitalization, there is an insufficient level of introduction of electronic information and educational resources. Therefore, this article discusses the stages of creating electronic information and educational resources and issues of organizing training based on them.